2002
DOI: 10.1002/hlca.200290000
|View full text |Cite
|
Sign up to set email alerts
|

The αL‐Threofuranosyl‐(3′→2′)‐oligonucleotide System (‘TNA'): Synthesis and Pairing Properties

Abstract: Dieter Seebach zum 65. Geburtstag gewidmet Our studies of a-l-Threofuranosyl-(3' 3 2')-oligonucleotides (−TNA×) are part of a systematic experimental inquiry into the base-pairing properties of potentially natural nucleic acid alternatives taken from RNA×s close structural neighborhood. TNA is an efficient Watson-Crick base-pairing system and has the capability of informational cross-pairing with both RNA and DNA. This property, together with the system×s constitutional and (presumed) generational simplicity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
160
0
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(169 citation statements)
references
References 59 publications
(54 reference statements)
4
160
0
5
Order By: Relevance
“…Threose nucleosides 2 such as PMDTA (1) and PMDTT (2) have been synthesized (Figure 1) because they can be assembled from natural precursor molecules. 3 Recently, we have synthesized threosyl 5'-deoxyphosphonic acid purine analogues. 4 It has been demonstrated that threose nucleic acids (TNA) form duplex with DNA and RNA of thermal stability, similar to that of the natural nucleic acid association.…”
Section: Introductionmentioning
confidence: 99%
“…Threose nucleosides 2 such as PMDTA (1) and PMDTT (2) have been synthesized (Figure 1) because they can be assembled from natural precursor molecules. 3 Recently, we have synthesized threosyl 5'-deoxyphosphonic acid purine analogues. 4 It has been demonstrated that threose nucleic acids (TNA) form duplex with DNA and RNA of thermal stability, similar to that of the natural nucleic acid association.…”
Section: Introductionmentioning
confidence: 99%
“…Of these compounds, threose nucleosides, 2 such as, PMDTA (1) and PMDTT (2), have been previously synthesized ( Figure 1) because they can be assembled from natural precursors. 3 Furthermore, it has been demonstrated that threose nucleic acids (TNA) form duplexes with DNA and RNA that are thermally stable, in an analogous manner to natural nucleic acid association. The triphosphates of threose nucleosides are substrates of several polymerases, and can be enzymatically incorporated into DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Threose phosphonate nucleosides 6 such as PMDTA (1) and PMDTT (2) have been synthesized (Figure 1) because they can be assembled from natural precursor molecules. 7 It has been demonstrated that threose nucleic acids (TNA) form duplex with DNA and RNA of thermal stability, similar to that of the natural nucleic acid association. The phosphonoalkoxy group of the proposed threose nucleoside phosphonates is bound at the 3'-position, bring the phosphorus atom and the nucleobase closer to each other than in previously synthesized nucleoside phosphonates where the phosphonate group is bound to the primary hydroxyl group of the nucleoside.…”
Section: Introductionmentioning
confidence: 99%